Lightning induced atrial fibrillation - Dronacharya, L; Poudel, R (Kathmandu University Medical Journal, 2009)
Atrial fibrillation (AF) is a common arrhythmia that occurs in paroxysmal and persistent forms. It occurs in varied situations but lightning induced AF is extremely rare. Here is a case which reverted to sinus rhythm spontaneously. This 37-year-old man without any underlying heart disease had new onset AF after being struck by a lightning. Oral Metoprolol alone was given to control ventricular rate. Spontaneous reversion to sinus rhythm within 36 hours is in favor of new onset lightning induced AF. Key words: Lightning injuries, atrial fibrillation, ECG changes doi: 10.3126/kumj.v6i4.1747 Kathmandu University Medical Journal (2008), Vol. 6, No. 4, Issue 24, 5514-515